Staffing of psychological and pedagogical support in the system of general education and secondary vocational education - Yu.V. Tukfeeva; T.P. Knisheva; A.P. Trofimova; A.K. Sharapova; V.V. Kurbanova (Психолого-педагогические исследования)
This article is a continuation of the first part of the description of the results of monitoring the functional model of psychological service in the system of general education and secondary vocational education in the Russian Federation. The article presents research materials on the staffing of psychological and pedagogical support in the education system. The monitoring was carried out using the stratification method, by allocating one subject of the Russian Federation from each Federal District for further research. The study involved 2288 respondents from 1979 organizations. According to the monitoring results, it was found that most often the psychological service includes a teacher-psychologist and a speech therapist. The traditional and situational form of mentoring is predominant, with almost half of the mentors having more than 20 years of professional experience. The degree of accessibility of supervision/intervention for teachers was also revealed (almost half of the study participants have the opportunity to participate in supervision/intervention). The motivation for the participation of teachers-psychologists in professional skills competitions is determined – the exchange of experience, professional development and improvement of professional skills. It is shown that some of the participants have access to digital platforms that allow them to carry out professional activities, but almost a third do not have suitable digital tools. The data obtained during the Monitoring regarding the staffing of psychological and pedagogical support will be used in the development of sample projects of a functional model of psychological service in the system of general education and secondary vocational education.